The formation of values from the physical education class - Eduardo Armando Prieto Tamarit; Juan José Hernández; Elsa Giniebra Enríquez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2018)
The article deals with the formation of values in the students of Primary Education from Physical Education classes, which is one of the elements that should receive special attention in the teaching-learning process, starting from the unity between the instruction and education that should characterize this process. That is why the authors focus attention on the methodological treatment that occurs in Physical Education classes to the formation of values in the students of Primary Education. For the development of the research methods were used: analysis-synthesis, induction-deduction, historical-logical, observation, documentary review, survey and descriptive statistics. The processing of the information referring to the formation of values in the students of this age and fundamentally in the classes of Physical Education was carried out; as well as the difficulties that arise with its methodological treatment. This allowed an assessment of the difficulties and potentials present in the process of values formation in Physical Education classes, which led to a set of actions. Hence, the objective of this article is to propose a set of actions that allow to take advantage of the potential of Physical Education to contribute to the formation of values in students of Primary Education.